The Intentionality of Promotional Patterns in Pre-Islamic Poetry "A Selected Reading of al-Muthaqqib al-ʿAbdī’s Nooniyyah" - Abdul Hussein Mariwish, Haitham ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
This study investigates the promotional intentionality embedded in pre-Islamic poetry through a selected examination of al-Muthaqqib al-ʿAbdī’s Nooniyyah. It analyzes how the poet deploys discourse structures and rhetorical–stylistic mechanisms to foreground the poetic self and construct a persuasive image. The study traces manifestations of symbolic promotion within the poem, whether through celebrating achievements, shaping the image of the group, or reinforcing the moral and social values prevalent in pre-Islamic society especially in passages concerning the beloved, the women of the caravan, the she-camel, and ʿAmr ibn Hind. A central existential truth is voiced through the she-camel: life is governed by the dialectic of settlement and departure. In settlement, the poet’s pleasure and gratification emerge through human closeness and familiarity with family and friends; in departure, his pain and sorrow intensify because it entails grievous separation and the severing of bonds of kinship and intimacy. The poet relies on suggestion and affective projection by transferring his emotions onto the she-camel, so that she becomes an inner voice articulating his psychological state; her moans and suffering serve as an authentic symbolic enactment of the bitterness and grief within him. Consequently, the poem performs a powerful communicative function, using emotionally charged symbolism to attract the recipient and secure engagement. Methodologically, the study adopts an analytical approach that combines stylistic and semantic perspectives to demonstrate the effectiveness of promotion within the poem’s structure and to clarify the mechanisms through which poetic discourse is oriented toward influencing and winning over the audience. DOI: https://doi.org/10.54633/2333-024-057-015